Impact of COVID-19 pandemic on the mental health of children and adolescents: a review - Santos, Glauce Gabriela; Vano, Vitor; Freitas, Vinicius; Palma, Sonia Maria (Brazilian Journal of Global Health, 2022)
OBJETIVO: A imprevisibilidade da pandemia de Coronavírus de 2019 (COVID-19) mudou a dinâmica socioeconômica em todo o mundo. Os resultados preliminares sugerem que todo o contexto da pandemia aumenta o risco de problemas psicológicos. A população infantil, embora menos estudada, é também vulnerável aos efeitos da pandemia. Esta revisão reúne os estudos publicados em 2020 com o objetivo de avaliar o impacto da pandemia na população infantil. MÉTODOS: Um total de 15 estudos que avaliaram a saúde mental de menores de 18 anos durante a pandemia de COVID-19 foram selecionados e analisados. RESULTADOS: Há um aumento de sintomas de ansiedade e depressão na população infantil e nos seus cuidadores na quarentena, com um elevado risco de progressão para perturbações mentais. No entanto, não há forma de avaliar a prevalência de perturbações mentais nesta população devido aos estudos que estão sendo conduzidos utilizando questionários em linha. CONCLUSÃO: Os profissionais de saúde devem estar atentos à possível presença de ansiedade e sintomas depressivos secundários ao isolamento social, especialmente em crianças com doenças crônicas ou em situações de vulnerabilidade. São necessários estudos futuros para determinar a prevalência, o risco e os possíveis tratamentos de doenças relacionadas ao estresse. DESCRITORES: Saúde Mental, Quarentena, Isolamento, Cuidador. ABSTRACT OBJECTIVE: The unpredictability of the Coronavirus Disease 2019 (COVID-19) pandemic has changed the socioeconomic dynamics around the world. Preliminary findings suggest that the entire context of the pandemic increases the risk of psychological problems. The child population, although less studied, is also vulnerable to the effects of the pandemic. This review brings together the studies published in 2020 aiming to assess the impact of the pandemic on the child population. METHODS: A total of 15 studies that evaluated the mental health of subjects under 18 years old during the pandemic of COVID-19 were selected and analyzed. RESULTS: There is an increase in anxious and depressive symptoms in the child population and in their caregivers with quarantine, with a high risk of progressing to mental disorders. However, there is no way to assess the prevalence of mental disorders in this population due to the studies being conducted using online questionnaires. CONCLUSION: Health professionals must be alert to the possible presence of anxiety and depressive symptoms secondary to social isolation, especially in children with chronic diseases or in situations of vulnerability. Future studies are needed to determine the prevalence, risk, and possible treatments for stress-related illnesses. DESCRIPTORS: Mental Health, Quarantine, Isolation, Caregiver.